From Text to Context: Building an Inclusive Organizational Culture in Islamic Boarding School-Based Higher Education Institutions - Kadi, Titi; Tamam, Badrut (JURNAL AL-TANZIM, 2024)
This study aims to analyze the management of the cultivation of Wasathiyah Islamic values in Islamic boarding school-based universities. This study uses a qualitative approach with a case study type. Data collection techniques used include in-depth interviews, observation, and documentation. Data were analyzed through three stages: data condensation, data presentation, concluding, and verifying the findings. The study results indicate that the management of the cultivation of Wasathiyah values in universities is integrated into curriculum planning and campus management, which reflects the principles of religious moderation and diversity. Both universities emphasize role models as the primary method in teaching, with Wasathiyah values implemented in the curriculum and applied in campus life through attitudes of tolerance and inclusivity. Evaluation of the cultivation is carried out periodically to assess the impact and suitability of the program with student needs. This study provides implications for integrating religious moderation values in Islamic boarding school-based higher education to create an inclusive, tolerant academic environment and build moderate character among students. The Wasathiyah-based curriculum can be a model for other universities to develop education that supports religious harmony and social tolerance.